Hazmat - Ollhoff, Jim (Minneapolis, MN : ABDO Pub. Co., 2013)
Presents information about hazardous materials and hazmat technicians, including the nine classes of hazardous materials, what a hazmat suit is made of, and what hazmat training consists of.
The Hazmat professional -- What are hazmats? -- Classes of hazmats -- What is a hazmat technician? -- Calm, cool, and collected -- Training -- Hazmat interview -- The hazmat suit -- How to clean up a nuclear disaster.
Includes index.
Keywords: Hazardous substances; Hazardous waste site remediation; Hazardous waste management industry; Pollution control industry; Hazardous occupations